PENGARUH PENGGUNAAN GOOGLE CLASSROOM PADA MATA PELAJARAN FISIKA TERHADAP HASIL BELAJAR SISWA DI SMA TONDANO KOTA - Meidy Atina Kuron; Arnold Harold Umboh; Regina N Pakpahan (SOSCIED, 2023)
The reseacrh of effect using Google Classroom as an LMS learning on student learning outcomes in Tondano City is an experiments carried out at several schools in Tondano City where the used of online learning platforms has been widely used by students due to the Covid-19 pandemic in 2020 in Indonesia.. This research was conducted at SMA Negeri 1 Tondano and SMA Negeri 3 Tondano with the sample chosen not randomly but with a specific aim, namely to see the equality between the control class and the experimental class. The purpose of this study was to determine the effect of using google classroom as an online learning application on student learning outcomes in Tondano City. The research method used is a quasi-experimental research with the form of nonequivalent control group design where there is one experimental group and one comparison group or control group by being given tests before and after treatment (treatment). Data on cognitive learning outcomes were analyzed using parametric statistics, namely the calculated homogeneity test, normality test, t test and N-gain, so it can be concluded that there is an effect of using Google Classroom on the learning outcomes of High School Students in Tondano City